The effects of a gamified morphological awareness intervention on students' cognitive, motivational and affective outcomes. (7th January 2022) - Qiao, Shen; Yeung, Susanna Siu‐sze; Shen, Xiaoai; Chu, Samuel Kai Wah
Abstract: Purpose : Morphological awareness (MA), the ability to reflect on and manipulate the smallest language units within a word, has been identified as an essential metalinguistic awareness to predict literacy development. In this study, we examine whether an online gamified English MA programme is more effective than physical face‐to‐face instruction in terms of cognitive, motivational and affective learning outcomes. Method : We applied a quasi‐experimental design using a sample of 33 students in an intervention group (gamified MA programme) and 49 in a control group (face‐to‐face programme). Both programmes were 8 hours in duration (30 minutes/session for 16 sessions). Students' cognitive, motivational and affective learning outcomes were evaluated before and after delivery of the programmes. We took an exploratory sequential mixed‐methods approach, in which qualitative data from semi‐structured interviews were used to validate the quantitative results. Results : The intervention group performed significantly better than the control group in MA and intrinsic motivation. No differences were found for word reading, reading comprehension or affective engagement. The qualitative analyses of the interview responses revealed in detail the students' perceptions of gamified learning. Conclusion : The findings provide evidence for the beneficial effects of gamified learning experiences in terms of cognitive and motivational outcomes in comparison to face‐to‐face instruction. Practitioner notes What is already known about this topic Morphological awareness (MA) is identified as a crucial reading‐related skill that relates to students' word reading and reading comprehension. However, few studies can be found that have investigated the use of gamification to teach MA. Gamification is emerging as a popular approach to motivate learners and facilitate learning. However, limited evidence has been presented of its effects on students' cognitive, motivational and affective outcomes, and no clear theoretical framework for gamified MA learning designs has been established. What this paper adds In this study, the effects of gamified and face‐to‐face morphology programmes were compared. Self‐determination theory was applied to gamification design and the meta design theory 'First Principles of Instruction' was applied in the development of online MA activities. Gamified morphology programme is more effective than a face‐to‐face programme on students' cognitive and motivational outcomes. Implications for practice and/or policy This study advances the pedagogical design of gamified learning, which can be applied to the teaching of reading‐related skills such as MA. Both appropriate uses of game design elements and theory‐driven instructional design are important to the success of gamified learning. Future studies should investigate the design of gamification that encourage collaboration and support low‐achieving students.